Relationship Between Remnant Pancreatic Volume and Endocrine Function After Pancreaticoduodenectomy. Issue 2 (February 2022) - Yamazaki, Tatsuya; Aoki, Takeshi; Tashiro, Yoshihiko; Koizumi, Tomotake; Kusano, Tomokazu; Matsuda, Kazuhiro; Fujimori, Akira; Yamada, Kosuke; Nogaki, Koji; Hakozaki, Tomoki; Wada, Yusuke; Shibata, Hideki; et al.
Background: Decreased pancreatic volume (PV) is a predictive factor for diabetes mellitus (DM) after surgery. There are few reports on PV and endocrine function pre- and post-surgery. We investigated the correlation between PV and insulin secretion. Methods: Seventeen patients underwent pancreaticoduodenectomy (PD) Pre- and post-surgery PV and C-peptide index (CPI) measurements were performed. Additionally, the correlation between PV and CPI was analyzed. Results: The mean preoperative PV (PPV) was 55.1 ± 31.6 mL, postoperative remnant PV (RPV) was 25.3±17.3 mL, and PV reduction was 53%. The mean preoperative C-peptide immunoreactivity (CPR) was 1.39 ± .51 and postoperative CPR was .85±.51. The mean preoperative CPI was 1.29±.72 and postoperative CPI was .73 ± .48. Significant correlations were observed between RPV and post CPR (ρ = .507, P = .03) and post CPI (ρ = .619, P = .008). Discussion: There was a significant correlation between RPV and CPI after PD. A smaller RPV resulted in lower insulin secretion ability, increasing the potential risk of new-onset DM after PD.